Simulation in Higher Education: A sociomaterial view - Hopwood, N.; Rooney, D.; Boud, D.; Kelly, Michelle (Routledge, 2016)
This article presents a sociomaterial account of simulation in higher education. Sociomaterial approaches change the ontological and epistemological bases for understanding learning and offer valuable tools for addressing important questions about relationships between university education and professional practices. Simulation has grown in many disciplines as a means to bring the two closer together. However, the theoretical underpinnings of simulation pedagogy are limited. This paper extends the wider work of applying sociomaterial approaches to educational phenomena, taking up Schatzki’s practice theory as a distinctive basis for doing so. The question ‘What is being simulated?’ is posed, prompting discussion of multiple bodies, performances and experiences. The potential of adopting such a framework for understanding simulation as a pedagogic practice that brings the classroom and workplace together is illustrated with reference to clinical education in nursing.